Ekonomiska konsekvenser av kriget i Ukraina: En studie av BNP-tillväxt i europeiska länder - Jönsson,Hanna; Malm,Elin (2025)
This paper examines the effects of Russia's invasion of Ukraine on economic growth in nine European countries. The countries are divided into primary neighbours (directly bordering Ukraine) and secondary neighbours (geographically close but not sharing a border). Using data from 1996 to 2023, 18 country-by-country regressions have been conducted as well as two panel data regressions to test three hypotheses related to impact on economic growth. The overall result shows limited empirical support for the hypothesis. No significant effects were found for GDP growth for either primary or secondary neighbours following the war. While growth coefficients for neighbouring countries were consistently negative, they were statistically insignificant. Some non-neighbouring countries showed positive trends, but without significance. In contrast, effects related to trade showed more consistent results. However, the reliability of the results can be questioned due to the relatively short post-war timeframe, leading to some effects being underestimated in our analyses. For future research, it is recommended that data is collected for a longer period of time after the war.
Keywords: Economic growth; Ukraine; war; spillover-effects; primary & secondary neighbours